Ozone Production in the Soberanes Smoke Haze: Implications for Air Quality in the San Joaquin Valley During the California Baseline Ozone Transport Study. Issue 11 (4th June 2020) - Langford, Andrew O.; Alvarez, Raul J.; Brioude, J.; Caputi, Dani; Conley, Stephen A.; Evan, S.; Faloona, Ian C.; Iraci, Laura T.; Kirgis, Guillaume; Marrero, Josette E.; Ryoo, Ju‐Mee; Senff, Christoph J.; et al.
Abstract: The Soberanes Fire burned 53, 470 ha (132, 127 acres) along the central California coast between 22 July and 12 October 2016, generating dense smoke and a variety of gaseous compounds that drifted eastward into the San Joaquin Valley Air Basin (SJVAB), an "extreme" nonattainment area for ozone (O3 ). These gases included nitrogen oxides (NO x ) and volatile organic compounds, the photochemical precursors of O3 . The fire started during the California Baseline Ozone Transport Study, a field campaign that brought aircraft, surface, and remote sensing measurements of O3 and related species to central California. In this paper, we use the California Baseline Ozone Transport Study measurements to assess the impact of the Soberanes Fire on ozone and particulate air quality in the SJVAB. We focus our analysis on 27 July to 2 August when the smoke haze was heaviest and the highest O3 concentrations in the SJVAB during 2016 were recorded. Our analyses suggest that while 40 to 60 ppbv of fire‐generated O3 was transported to the eastern SJVAB in the 1‐ to 3‐km‐altitude range, relatively little smoke or fire‐generated O3 reached the surface in the Visalia area. Key Points: Aircraft and remote sensing measurements are used to investigate impacts of the Soberanes Fire on air quality in the San Joaquin Valley Ozone enhancements in excess of 50 ppbv were measured by both lidar and aircraft between 1 and 3 km above the surface No significant enhancements in surface ozone were observed